Development of the Surgical Patient safety Observation Tool (SPOT). Issue 3 (3rd April 2018) - Heideveld‐Chevalking, A. J.; Calsbeek, H.; Emond, Y. J.; Damen, J.; Meijerink, W. J. H. J.; Hofland, J.; Wolff, A. P.
Abstract : Background: A Surgical Patient safety Observation Tool (SPOT) was developed and tested in a multicentre observational pilot study. The tool enables monitoring and benchmarking perioperative safety performance across departments and hospitals, covering international patient safety goals. Methods: Nineteen perioperative patient safety observation topics were selected from Dutch perioperative patient safety guidelines, which also cover international patient safety goals. All items that measured these selected topics were then extracted from available local observation checklists of the participating hospitals. Experts individually prioritized the best measurement items per topic in an initial written Delphi round. The second (face to face) Delphi round resulted in consensus on the content of SPOT, after which the measurable elements (MEs) per topic were defined. Finally, the tool was piloted in eight hospitals for measurability, applicability, improvement potential, discriminatory capacity and feasibility. Results: The pilot test showed good measurability for all 19 patient safety topics (range of 8–291 MEs among topics), with good applicability (median 97 (range 11·8–100) per cent). The overall improvement potential appeared to be good (median 89 (range 72·5–100) per cent), and at topic level the tool showed good discriminatory capacity (variation 27·5 per cent, range in compliance 72·5–100 per cent). Overall scores showed relatively little variation between the participating hospitals (variation 13 per cent, range in compliance 83–96 per cent). All eight auditors considered SPOT a straightforward and easy‐to‐use tracer tool. Conclusion: A comprehensive tool to measure safety of care was developed and validated using a systematic, stepwise method, enabling hospitals to monitor, benchmark and improve perioperative safety performance. Abstract : A Surgical Patient safety Observation Tool (SPOT) was succesfully developed and tested in a multicentre observational pilot‐study. The tool enables monitoring and benchmarking of perioperative safety performance across departments and hospitals, covering (inter)national patient safety goals. Merits evaluation in other countries